Developing of honeycomb shaped cordierite ceramic from indigenous raw materials and its characterization - Begum S.; Misran H.; Aminuddin A. (2023)
Cordierite ceramic of chemical composition 2MgO-2Al2O 3-5SiO2 has low value of thermal expansion, excellent thermal shock resistance, high porosity and high strength. The exhibited properties resulted wide range of industrial applications, especially in the catalytic converter, kiln furniture, diesel particulate filter and high frequency insulator. It occurs rarely in nature and its formulation from the indigenous raw materials is sensitive to the peak sintering temperature and holding time. Both the parameters are again affected on the source of raw materials. Hence optimization of peak temperature and holding time is crucial for each source of raw materials. In this paper three indigenous raw materials, clay, kaolin and talc were taken and mixed with different dopants. The prepared powder batch was sintered at different peak temperature and holding time. Among the three indigenous raw materials kaolin was found to be most suitable to formulate cordierite. The peak temperature was varied within the range of 1340C -1400C and the holding time was considered from 30 minutes to 90 minutes. Both the parameters had significant influence on the production of cordierite. The percent of cordierite formation was affected with both the variation of holding time and peak temperature. Tough thermal shock resistance was not influenced by any of the parameters, but the influence on the porosity was quite significant. The green body was also prepared from calcined powder batch and was sintered at different peak temperature. Calcination did not exhibit any affect on cordierite formulation. (2011) Trans Tech Publications, Switzerland.